The Raven por Machado de Assis e Fernando Pessoa - Hensel, Greicy Kelly de Oliveira (2015)
The translational activity is necessary in all fields of knowledge. Being poetry a text of aesthetic nature, it is not difficult to understand that the translation of poetic texts is the critical point of translation problems. Many poets are against this activity, they question the poetry translatability. The theme of this research is the translation of poetic texts, and the guiding question of the work is: knowing that elements such as rhyme, repetition, assonance, alliteration are important in the construction of the poetic text and hardly translated from one language to another, would there be an specific way for poetry translation? The overall goal is to understand how the translation of poetic texts works, in other words, to understand whether structural and stylistic elements such as the number of verses and stanzas, rhymes, the sound - are preserved or recreated in the translated text, or it preserves only the content. Therefore, this research presents an analysis of the poem The Raven by Edgar Allan Poe and its translated versions by Machado de Assis and Fernando Pessoa. They were analyzed from the perspective of greimasian semiotic theory, a theory of meaning, which seeks to explain the meanings of texts from a generative process of meaning structured into four levels: fundamental, narrative, discursive and manifestation. They also sought grounding in the theories of translation. Within this theoretical scope, it was realized that there is a literal translation and the recreation / transcreation (to master the source and arrival language, extract what is essential and recreate it), covered in this study by Haroldo de Campos (1994) and Augusto de Campos (2011), the latter being the technique used in the translation of poetry. In the light of semiotic theory, it is noticed that in the recreation of poetic texts it is possible to preserve the fundamental and narrative levels, more abstract levels of organization of content, where the structures do not change. The greatest difficulty is in discursive and manifestation levels, which involve choices of words and stylistic issues. At these levels, some elements may be maintained, but necessarily, others are modified, it is impossible to maintain the identity of rhyme, assonance, alliterations, repetitions of the original, since the meaningful words are different in each language. The analysis also allows us to say that Pessoa sought to be more faithful to the compositional form (kept the same number of stanzas, verses and the rhyme scheme) of the original poem unlike Machado (who kept the number of stanzas, but changed significantly the number of verses and the rhyme scheme). However, in both versions, other elements of the manifestation level (rhymes, assonance, alliteration) have been recreated. It follows, then, that in the recreation the essential content of the text is preserved, but elements of discursive and manifestation levels are modified, especially the manifestation elements, these related to subjective choices and constraints of each language system